Joining of plastics : handbook for designers and engineers - Rotheiser, Jordan, ....- (Munich : Hanser, 2009)
The third edition of this comprehensive handbook emphasizes the relationship between the assembly methods, the materials, and the plastics manufacturing processes, thus enabling the reader to identify the best design/assembly method for a given application. The book has been completely updated and a new chapter on laser welding of plastics has been added. All principal fastening and joining methods used to assemble plastic parts today are described with their particular advantages and disadvantages. Assembly method limitations for a given material and/or a given molding process are discussed in great detail. This is very much a how-to book, offering a wealth of hard-to-find detailed information.
With index